Peran Kepemimpinan Dalam Pengembangan Sistem Bimbingan dan Konseling di Lingkungan Pendidikan - Syahwitri, Febri Adhari; Nasution, Inom; Anissa, Nur; Aulia, Najwa; Mahisani, Tiara Putri (Madani: Jurnal Ilmiah Multidisiplin, 2024)
This research aims to find out the role of leadership in developing guidance and counseling systems in the educational environment. a leader who plays an important role in developing the guidance and counseling system in his school environment to create quality education. Quality education consists of three elements: management and leadership, educational learning, and independent guidance and counseling. Guidance and counseling is a way to ensure that education is carried out well through the education system. Leaders are also the ones who overcome various problems that exist in schools. Good leadership must be able to motivate, inspire and direct all school members towards the vision and mission that have been set. In writing this scientific article, the method used in this research is the method of collecting library data by reading, taking notes and processing research data which is then concluded as research material. The research results show that the role of the school principal in developing the guidance and counseling system in the school environment, the efforts made by the leader are carrying out the role as a leader by making plans and deliberating; as a manager by creating collaboration between guidance and counseling teachers to support the implementation of counseling guidance in schools.